2009
DOI: 10.1002/yea.1742
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70/Hsp90 co‐chaperones are required for efficient Hsp104‐mediated elimination of the yeast [PSI+] prion but not for prion propagation

Abstract: The continued propagation of the yeast [PSI(+)] prion requires the molecular chaperone Hsp104 yet in cells engineered to overexpress Hsp104; prion propagation is impaired leading to the rapid appearance of prion-free [psi(-)] cells. The underlying mechanism of prion loss in such cells is unknown but is assumed to be due to the complete dissolution of the prion aggregates by the ATP-dependent disaggregase activity of this chaperone. To further explore the mechanism, we have sought to identify cellular factors r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 62 publications
3
57
0
1
Order By: Relevance
“…The Hsp90 chaperone system, which serves as a post-translational regulator of many cellular processes, is also important for the curing mechanism. 30,31 Increasing Hsp90 abundance does not affect curing by overexpressed Hsp104. 32 However, although neither deleting Hsp70/ Hsp90 coordinating co-chaperone Sti1p nor chemical inhibition of Hsp90 affect [PSI + ] propagation, either treatment strongly inhibits the curing.…”
Section: Hsp104mentioning
confidence: 99%
“…The Hsp90 chaperone system, which serves as a post-translational regulator of many cellular processes, is also important for the curing mechanism. 30,31 Increasing Hsp90 abundance does not affect curing by overexpressed Hsp104. 32 However, although neither deleting Hsp70/ Hsp90 coordinating co-chaperone Sti1p nor chemical inhibition of Hsp90 affect [PSI + ] propagation, either treatment strongly inhibits the curing.…”
Section: Hsp104mentioning
confidence: 99%
“…These and other data are consistent with a distinction between processes of prion propagation and curing and a difference in mechanism of curing by Hsp104 inhibition and overexpression. We and others recently showed that extragenic suppressors of the Ssa1-21p inhibition of [PSI 1 ] also suppress the ability of overexpressed Hsp104 to cure cells of [PSI 1 ] (Moosavi et al 2010;Reidy and Masison 2010), which implies Ssa1-21p and elevated Hsp104 antagonize [PSI 1 ] by a similar mechanism.…”
mentioning
confidence: 92%
“…Notably, replacing the M-domain of bacterial ClpB with that of its yeast homolog Hsp104 switched the species specificity of the bichaperone system so that ClpB now cooperated with the eukaryotic Hsp70/40 system and vice versa (7,27). The role of the M-domain in mediating DnaKJ/GrpE interaction is consistent with the M-domain being on the outside of the ClpB hexamer (5, 8), but incompatible with the previously proposed structure of yeast Hsp104 (28,29), which placed the M-domains on the interior or intercalated between subunits.Although we recently showed that ClpB and Hsp104 share a similar 3D structure (30), functional differences exist (19,(31)(32)(33). Moreover, it remains unclear how ClpB exerts the ATP power stroke to thread substrates through the ClpB hexamer ring, and how ClpB unfolds substrates that are typically much larger than the ClpB hexamer itself.…”
mentioning
confidence: 99%
“…Although we recently showed that ClpB and Hsp104 share a similar 3D structure (30), functional differences exist (19,(31)(32)(33). Moreover, it remains unclear how ClpB exerts the ATP power stroke to thread substrates through the ClpB hexamer ring, and how ClpB unfolds substrates that are typically much larger than the ClpB hexamer itself.…”
mentioning
confidence: 99%